How do you find the remainder term #R_3(x;1)# for #f(x)=sin(2x)#?

Answer 1

Final Term of the Taylor Series

#R_n(x;c)={f^{(n+1)}(z)}/{(n+1)!}(x-c)^{n+1}#,
where #z# is a number between #x# and #c#.
Let us find #R_3(x;1)# for #f(x)=sin2x#.

Through the use of derivatives,

#f'(x)=2cos2x# #f''(x)=-4sin2x# #f'''(x)=-8cos2x# #f^{(4)}(x)=16sin2x#

Thus, we have

#R_3(x;1)={16sin2z}/{4!}(x-1)^4#,
where #z# is a number between #x# and #1#.

I hope you found this useful.

Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer 2

To find the remainder term ( R_3(x;1) ) for ( f(x) = \sin(2x) ) using the Taylor series expansion centered at ( a = 1 ), follow these steps:

  1. Find the first few derivatives of ( f(x) = \sin(2x) ) evaluated at ( a = 1 ):

[ f(x) = \sin(2x) ] [ f'(x) = 2\cos(2x) ] [ f''(x) = -4\sin(2x) ] [ f'''(x) = -8\cos(2x) ]

  1. Evaluate these derivatives at ( a = 1 ):

[ f(1) = \sin(2) ] [ f'(1) = 2\cos(2) ] [ f''(1) = -4\sin(2) ] [ f'''(1) = -8\cos(2) ]

  1. Use the Taylor series formula to find the remainder term ( R_3(x;1) ):

[ R_3(x;1) = \frac{f'''(c)}{3!} \cdot (x - 1)^3 ]

where ( c ) is some value between ( 1 ) and ( x ).

  1. Substitute the values of the derivatives and ( x ):

[ R_3(x;1) = \frac{-8\cos(2)}{6} \cdot (x - 1)^3 ]

Simplify:

[ R_3(x;1) = \frac{-4\cos(2)}{3} \cdot (x - 1)^3 ]

This is the remainder term ( R_3(x;1) ) for ( f(x) = \sin(2x) ) centered at ( a = 1 ).

Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer 3

To find the remainder term ( R_3(x;1) ) for the function ( f(x) = \sin(2x) ), we use Taylor's theorem with remainder. In this case, we use the third-order Taylor polynomial, which is ( P_3(x) = f(1) + f'(1)(x - 1) + \frac{f''(1)}{2!}(x - 1)^2 + \frac{f'''(1)}{3!}(x - 1)^3 ), where ( f(1) = \sin(2) ), ( f'(1) = 2\cos(2) ), ( f''(1) = -4\sin(2) ), and ( f'''(1) = -8\cos(2) ). Then, the remainder term ( R_3(x;1) ) is given by ( R_3(x;1) = f(x) - P_3(x) ).

Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer from HIX Tutor

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

Not the question you need?

Drag image here or click to upload

Or press Ctrl + V to paste
Answer Background
HIX Tutor
Solve ANY homework problem with a smart AI
  • 98% accuracy study help
  • Covers math, physics, chemistry, biology, and more
  • Step-by-step, in-depth guides
  • Readily available 24/7